Secondary Students' Exposure to (Non) Yoruba Traditional Mass Media in Ibadan Metropolis: Educational Implications in a theoretical Perspective (2023)
The study assessed and compared secondary school students' exposure to Yoruba and non-Yoruba traditional mass media, as well as the educational implications. Three research questions were answered. The study adopted the survey research design. Three hundred and fifty (350) SS II students randomly selected from 10 public secondary schools in Ibadan metropolis responded to the self-made questionnaire titled Students' Questionnaire on Traditional Mass Media Exposure (r=.73). The data collected were analysed using descriptive statistics and t-test at 0.05 level of significance. Findings revealed that secondary students were highly exposed to Yoruba traditional mass media (weighted mean=3.27>2.50) and Non-Yoruba traditional media (weighted mean=2.91>2.50), with no significant difference in the two. The study concludes that if the Yoruba traditional mass media are more accessible and related to students' cognitive and affective need in Yoruba studies, students' exposure to them may increase. It is, therefore, recommended that traditional mass media companies should portray more of the Yoruba culture and heritage in their productions and services